Real-time balance assessment using multimodal sensors - Soh, Yu Jie (2016)
Gait is rhythmic and characterized by alternating propulsive and retropulsive motions of lower extremities. Gait phases include, stance phase (Heel Strike, Foot flat, Mid-stance, Heel Off, Toe Off) and swing phase (Acceleration, Mid-swing, Deceleration). The analysis of gait phases together with the gait parameters will help to understand a subject’s gait patterns and identify the abnormality while walking. Such gait assessment is usually done visually by therapists to interpret the quality of locomotion of subjects for identifying possible underlying pathologies. A good understanding of gait information could help to configure personalized rehabilitation regiment in order to prevent undesirable consequences of getting injuries from fall accidents. This project aims to provide a convenient, effective and affordable solution in performing gait assessment by patients. With the addition of infrared sensor, this project demostrates that the addition will provide in-depth, meaningful information to gait pattern analysis. Infrared sensor is an affordable sensor which can be purchased at a very low cost.